Tourist product in the segment of ecological tourism in Ukraine in today's conditions - V.V. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article deals with the state of development of ecological tourism in Ukraine. The resource potential for the development of ecological tourism in Ukraine is highlighted and the competitive advantages of ecological tourism in Ukraine are highlighted. An overview of existing ecological tourism products in Ukraine was carried out and new promising places for the development of ecological tourism were identified. Proposals for improving the ecological tourism product were provided.